Design and application of a multistage progressive ion transport interface phase
Patent Information
- Application Number
- CN202611200279.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]本发明的目的在于提供一种多级渐进离子传输界面相的设计及其运用,解决了现有技术中的金属电池中金属负极与电解液副反应严重、枝晶生长、体积膨胀以及界面不稳定制约电池性能和安全的问题
[0019]1、本发明通过在电极表面构筑分级渐进离子传输层来调控锂与锌电极表面的去溶剂化行为及离子传输行为,实现对金属电极的枝晶抑制作用,实现长寿命高性能电池的稳定工作,本发明制备成本低廉,操作条件简单且反应迅速,分级渐进离子传输层主要包括氟化物-合金无机相和电子绝缘但高离子传输有机聚合物相,该保护层同时具有聚合物的柔性,有效缓解金属负极在循环过程中的体积变化,以及无机物如合金保护层的刚性,加快了离子界面传输特性,有效防止枝晶刺破隔膜,提高了金属负极的稳定性和安全性,本发明中的制备方法新颖,一步法原位反应就可以构建分级式快离子传输聚合物-金属氟化物-合金复合保护结构的金属负极。
Smart Images

Figure CN122889706A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical energy technology, and in particular relates to the design and application of a multi-level progressive ion transport interface phase. Background Technology
[0002] In the field of electrochemical energy, with the booming development of emerging industries such as electric vehicles and home energy storage, the demand for high-energy-density energy storage batteries is increasing. Lithium metal, with its theoretical capacity of up to 3860 mAh / g and electrode potential as low as -3.040 V vs standard hydrogen electrode, and zinc metal, with a specific capacity of 820 mAh / g, have become strong candidates for next-generation power energy storage batteries. However, both face many challenges in practical applications as metallic anodes.
[0003] Lithium and zinc metals are highly chemically reactive, leading to severe side reactions with the electrolyte. This not only causes irreversible consumption of active materials and electrolyte, significantly shortening battery life, but also alters the internal composition of the battery, affecting its performance stability. Uneven deposition of metal atoms on the electrode surface results in dendrite formation. Dendrite growth can puncture the separator, causing short circuits, and is accompanied by severe volume expansion, damaging the battery structure and posing serious safety hazards. This has become a major obstacle to the commercialization of metal-based rechargeable batteries. Most organic or inorganic electrolytes are highly reactive under electrochemical conditions, causing instability at the interface between the metal electrode and the electrolyte. This unstable interface exacerbates the growth of metal dendrites and the volume expansion effect, severely reducing the battery's cycle performance and cycle life.
[0004] Currently, the existing technologies used to solve these problems have obvious shortcomings: Adding high-concentration electrolyte salts to create a molecular crowding strategy can alter the solvation structure of charge carriers at the electrolyte or electrode interface. However, this method significantly increases costs, increases electrolyte viscosity, and reduces ionic conductivity, leading to poorer battery rate performance and failing to meet the demands of rapid charge-discharge in practical applications. In metal batteries, the solid electrolyte interphase (SEI) film formed by the reaction of the active electrode with the organic electrolyte has a complex and uncontrollable composition. Its inhomogeneous structure and surface defects promote uneven deposition of metal atoms, while dendrite growth further damages the SEI structure, gradually increasing battery polarization and even triggering serious safety issues such as thermal runaway. Introducing an interface passivation layer can protect the metal electrode to some extent, but it suffers from high interface impedance, poor flexibility, and susceptibility to breakage and failure during long-term cycling. High interface impedance affects battery charge-discharge efficiency, while poor flexibility and susceptibility to breakage and failure prevent the battery from providing sustained protection during long-term cycling.
[0005] To address these issues, we present a design and application of a multi-level progressive ion transport interface phase. Summary of the Invention
[0006] The purpose of this invention is to provide a design and application of a multi-level progressive ion transport interface phase, which solves the problems of severe side reactions between the metal anode and the electrolyte, dendrite growth, volume expansion, and interface instability in existing metal batteries, which restrict battery performance and safety.
[0007] To solve the above-mentioned technical problems, the present invention is achieved through the following technical solution.
[0008] This invention relates to the design of a multi-level progressive ion transport interface phase, comprising the following steps: Step 1: Environmental Preparation Replace the atmosphere in the glove box with argon gas to ensure that the oxygen and moisture content in the box are both below 0.1 ppm. Prepare the metal fluoride, polymer, solvent, metal substrate, spin coater and drying equipment required for the experiment. The metal fluoride is one or more of SnF2, ZnF2, MgF2, FeF3, YF3 and MnF2. Step 2: Solution or gel preparation: Weigh out metal fluorides and polymers, and add them to a selected solvent according to a ratio of 0.01%-30% metal fluoride content and 5%-70% organic content. When preparing a modification solution for lithium sheets, mix ZnF2 and PVDF according to a ratio of 10% metal fluoride content, 50% organic content, and the remainder as PVP solvent. When using it for zinc sheets, mix MnF2 and PVDF according to a ratio of 15% metal fluoride content, 60% organic content, and the remainder as DMSO solvent. Step 3: Electrode spin coating: The metal substrate is fixed on the sample stage of the spin coater. 0.5 mL of the prepared solution is drawn up with a pipette and slowly dropped onto the center of the substrate surface. The spin coater is started and the solution is evenly spread on the substrate surface under the action of centrifugal force, forming a thin and uniform liquid film. Step 4: Drying process: After spin coating, remove the electrode with the modification film from the spin coater and place it in the drying area of the glove box. If static drying is used, let the electrode stand for 12 hours to allow the solvent to evaporate naturally. If vacuum treatment is required, place the electrode in a vacuum drying device at a vacuum degree of 10. -3 Drying at 30°C for 5 hours removes residual solvent and cures the modified layer, forming a composite ion-conducting polymer-metal fluoride-alloy layer on the surface of the metal anode.
[0009] The present invention is further configured such that, in step two, if multiple metal fluorides are mixed, the ratio between the metal fluorides is arbitrary, as long as the overall metal fluoride content after mixing is in the range of 0.01%-30%; if multiple polymers are mixed, the ratio between the polymers is also arbitrary, as long as the overall organic content after mixing is in the range of 5%-70%.
[0010] The present invention is further configured such that, in step three, the volume of solution drawn by the pipette can be adjusted within the range of 0.3-0.7 mL for metal substrates of different sizes, the rotation speed of the spin coater can be adjusted between 1500-2500 r / min, and the rotation time can be adjusted between 45-75 s, so as to ensure that a uniform liquid film can be formed on different substrates.
[0011] The present invention is further configured such that, in step four, for some special combinations of polymers and metal fluorides, if the static drying effect is not good, the mixture can be pre-dried in an oven at 40°C for 1 hour before static drying, followed by 12 hours of static drying; if vacuum drying is used, for easily oxidized metal fluorides, the vacuum degree can reach 10... -3 After Pa, a small amount of argon gas is introduced into the drying equipment to maintain the pressure at 10. -2 -10 -1 Between Pa, it is then dried at 30°C for 5 hours.
[0012] The present invention is further configured such that the polymer is one or more of the following polymers: polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene glycol, etc.; the solvent includes polyvinylpyrrolidone and dimethyl sulfoxide; the thickness of the metal substrate is between 0.1-0.5 mm; and the surface roughness Ra is between 0.05-0.2 μm.
[0013] The present invention is further configured such that, in step two, a nano-silica dispersion is added, the amount of which is 0.1%-0.5% of the total mass of the solution.
[0014] The present invention is further configured such that, in step four, the thickness of the formed composite ion-conducting polymer-metal fluoride-alloy layer is measured, and the thickness range should be between 50-500 nm. If the thickness does not meet the requirements, the solution concentration, spin-coating parameters and drying conditions can be adjusted according to the actual situation, and the preparation can be repeated.
[0015] The present invention is further configured such that the instruments and equipment used in the preparation process, such as the spin coater, magnetic stirrer and vacuum drying equipment, need to be calibrated and cleaned before each use to ensure that the performance of the instruments and equipment is stable and that there are no impurities contaminating the experimental materials. In step one, in addition to detecting the oxygen and moisture content in the glove box, the flow rate and purity of argon gas also need to be detected regularly. The argon gas flow rate should be maintained at 5-10 L / min and the purity should not be less than 99.999%.
[0016] The present invention is further configured such that, in step two, a magnetic stirrer is used to stir for 3 hours at 40°C and 500 r / min until a uniform solution is formed; and in step three, the spin coater rotates at 2000 r / min for 60 s.
[0017] A method for using a multi-level progressive ion transport interface phase includes the following steps: Step 1: Battery Component Pre-processing and Assembly Under the argon atmosphere in the glove box, the modified metal anode, cathode material and separator are first immersed in the electrolyte for 10-30 minutes to fully wet each component. Using 1M LiTFSI / DME:DOL (1:1) as the electrolyte, the pretreated modified metal anode and the corresponding cathode material and separator are stacked and assembled into a symmetrical cell or a full cell. During the assembly process, the coaxiality deviation of each component is controlled to not exceed 0.5mm. A uniform pressure of 0.1-0.3MPa is applied to ensure good contact between each component and no risk of short circuit. Step Two: Basic Electrochemical Impedance and Reversibility Tests After the assembled battery was statically activated for 24 hours, electrochemical impedance spectroscopy was performed using an electrochemical workstation. The electrochemical impedance spectrum of the battery was obtained under the conditions of frequency range of 0.01Hz-100kHz and amplitude of 5mV to analyze the effect of the modification layer on the interfacial impedance and charge transfer impedance. Cyclic voltammetry was performed with the scan rate set to 0.1-1mV / s and the voltage window set according to the battery system. The electrochemical reversibility and interfacial stability of the battery were evaluated by the peak shape, peak position difference and peak area of the redox peak. Step 3: Charge / discharge cycle and rate performance testing: The battery was subjected to constant current charge-discharge cycle tests at a set current density, and the charge-discharge specific capacity, initial coulombic efficiency, and coulombic efficiency per cycle were recorded. Rate performance tests were then conducted at different current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C, with 5-10 cycles at each current density to evaluate the ion transport capability of the modified layer at different current densities. Long cycle life tests were then conducted, with 100-1000 cycles at a 1C current density to examine the battery's capacity retention and interface stability. Step 4: Interface Characterization and Process Parameter Optimization The cycled battery was disassembled, and the morphology, composition, and mechanical properties of the interfacial phase on the surface of the metal anode were characterized using scanning electron microscopy, X-ray photoelectron spectroscopy, and atomic force microscopy. The evolution of the interfacial phase during cycling was analyzed. Based on the electrochemical performance test data and the interfacial characterization results, the solution ratio, spin coating parameters, drying conditions, and battery assembly process parameters in the interfacial phase preparation process were adjusted. The above steps were repeated until battery performance that meets the requirements of practical applications was obtained.
[0018] The present invention has the following beneficial effects.
[0019] 1. This invention regulates the desolvation and ion transport behavior of lithium and zinc electrodes by constructing a hierarchical progressive ion transport layer on the electrode surface, thereby suppressing dendrite formation in the metal electrode and achieving stable operation of a long-life, high-performance battery. This invention is inexpensive to prepare, has simple operating conditions, and reacts rapidly. The hierarchical progressive ion transport layer mainly comprises a fluoride-alloy inorganic phase and an electronically insulating but highly ion-transporting organic polymer phase. This protective layer simultaneously possesses the flexibility of a polymer, effectively mitigating volume changes in the metal anode during cycling, and the rigidity of inorganic materials such as alloy protective layers, accelerating ion interface transport characteristics, effectively preventing dendrites from piercing the separator, and improving the stability and safety of the metal anode. The preparation method in this invention is novel; a one-step in-situ reaction can construct a metal anode with a hierarchical fast ion transport polymer-metal fluoride-alloy composite protective structure. Attached Figure Description
[0020] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below.
[0021] Figure 1 The image shows the SEM image of the lithium metal anode modified with the polymer-lithium fluoride-alloy layer in Example 1.
[0022] Figure 2 This is a cross-sectional SEM image of the lithium metal anode modified with a polymer-lithium fluoride-alloy layer in Example 2.
[0023] Figure 3 The image shows the XRD pattern of the lithium metal anode modified with polymer-lithium fluoride-alloy layer in Example 3.
[0024] Figure 4 The image shows the optical images of the lithium metal surface before and after treatment in dry air in Example 4.
[0025] Figure 5 The images show the electrochemical impedance spectroscopy of lithium metal before and after treatment in Example 5.
[0026] Figure 6The image shows scanning electron microscope (SEM) images of the surfaces of the two types of lithium metals after cycling in Example 6.
[0027] Figure 7 The zinc metal anode modified with a composite hierarchical progressive ion-conducting polymer-zinc fluoride-alloy layer in Example 7 is shown.
[0028] Figure 8 The graph shows the electrochemical cycling performance of the symmetrical battery in Example 8.
[0029] Figure 9 This is a graph showing the electrochemical deposition dissolution efficiency of the battery in Example 9.
[0030] Figure 10 The graph shows the low-temperature electrochemical performance of the battery assembled with the modified electrode in Example 10. Detailed Implementation
[0031] The technical solutions of the present invention will be described below with reference to the accompanying drawings. The described embodiments are only some embodiments of the present invention, and not all embodiments.
[0032] Example 1: Preparation of modified lithium metal anode: In an argon environment with oxygen and moisture content controlled below 0.1 ppm in a glove box, weigh appropriate amounts of ZnF2 and polyvinylidene fluoride (PVDF) to make ZnF2 content 10% and PVDF content 50% (the remainder being polyvinylpyrrolidone (PVP) solvent). Mix them and add them to PVP. Stir with a magnetic stirrer at 40℃ and 500 r / min for 3 hours to prepare a homogeneous solution. Fix the lithium sheet on the sample stage of a spin coater and use a pipette to add 0.5 mL of the solution to the center of the lithium sheet surface. Set the spin coater rotation speed to 2000 r / min and the rotation time to 60 s. After spin coating, place the lithium sheet in the glove box to dry for 12 hours to obtain a lithium metal anode modified with a composite ion-conducting polymer-lithium fluoride-alloy layer.
[0033] Performance testing: SEM analysis was performed on the modified lithium metal anode to observe its surface microstructure. Compared with the original lithium metal anode, it was found that the modification layer uniformly covered the surface of the lithium metal anode, effectively improving the electrode surface condition. Figure 1 ) Example 2: Preparation of modified lithium metal anode: Under an argon atmosphere in a glove box with oxygen and moisture content both below 0.1 ppm, MgF2 and polydimethylsiloxane (PDMS) were weighed, with MgF2 comprising 12% and PDMS comprising 55%, dissolved in dimethyl sulfoxide (DMSO). The solution was stirred at 40℃ and 500 rpm for 3 hours to form a homogeneous solution. A lithium sheet was fixed on a spin coater, and 0.5 mL of the solution was added dropwise onto the lithium sheet. The spin coater parameters were set to 2000 rpm and 60 s rotation time. After spin coating, the solution was allowed to dry in a glove box for 12 hours to obtain the modified lithium metal anode.
[0034] Performance testing: Cross-sectional SEM analysis of the modified lithium metal anode revealed a uniform modification layer thickness and tight bonding with the lithium metal anode, providing a structural foundation for improved battery performance. Figure 2 ) Example 3: Preparation of modified lithium metal anode: Ensure the oxygen and moisture content in the argon atmosphere within the glove box is below 0.1 ppm. Weigh SnF2 and polyvinylidene fluoride-difluoropropylene (PVDF-HFP) to achieve a SnF2 content of 15% and a PVDF-HFP content of 60% (DMSO as solvent). Stir thoroughly in DMSO at 40℃, 500 rpm for 3 hours. Place the lithium sheet on the sample stage of a spin coater, add 0.5 mL of the solution, and spin coat at 2000 rpm for 60 seconds. Then dry in the glove box for 12 hours to obtain the modified lithium metal anode.
[0035] Performance testing: XRD analysis was performed on the modified lithium metal anode. The formation of the alloy phase in the modified layer was clarified by analyzing the XRD patterns, providing a theoretical basis for interpreting the performance of the modified layer. Figure 3 ) Example 4: Preparation of modified lithium metal anode: In a glove box with argon atmosphere where oxygen and moisture content both meet requirements (below 0.1 ppm), TiF2, polyvinylidene fluoride-difluoropropylene (PVDF-HFP), and polyethylene oxide were dissolved in DMSO at a ratio of 18% TiF2, 52% PVDF-HFP, and 8% polyethylene oxide (solvent: DMSO). The solution was stirred at 40°C and 500 rpm for 3 hours to prepare a homogeneous solution. 0.5 mL of this solution was spin-coated onto a lithium sheet at 2000 rpm for 60 s, and dried for 12 hours to obtain the modified lithium metal anode.
[0036] Performance testing: The surface changes of the lithium metal electrodes before and after modification were observed in dry air. The results showed that the surface change of the modified lithium metal electrode in dry air was significantly less than that of the original lithium metal electrode, indicating that the modification layer effectively inhibited the reaction between lithium metal and air, providing good protection for the lithium metal. Figure 4 ) Example 5: Preparation of modified lithium metal anode and assembly of battery: In a glove box argon environment with oxygen and moisture content below 0.1 ppm, the preparation method is the same as in Example 2. Using 1M LiTFSI / DME:DOL (1:1) as electrolyte, the modified lithium metal anode and the original lithium metal anode are assembled into symmetrical batteries respectively.
[0037] Performance testing: Electrochemical impedance spectroscopy was performed on the assembled symmetrical battery. The results showed that the modified lithium metal electrode exhibited a significant reduction in electrochemical impedance, indicating a decrease in internal resistance and thus improving the battery's charge and discharge efficiency. Figure 5 ) Example 6: Preparation of modified lithium metal anode and assembly of battery: Modified lithium metal anode was prepared in a glove box with argon atmosphere (oxygen and moisture content below 0.1 ppm) according to the method in Example 4. A symmetrical battery was assembled with the original lithium metal anode using 1 M LiTFSI / DME:DOL (1:1) as the electrolyte.
[0038] Performance testing: at 3mA / cm 2 At a given current density, the assembled symmetrical battery underwent a 300-hour deposition and dissolution cycle test. After the cycle, the battery was disassembled to observe the electrode morphology. The original lithium electrode surface was found to be relatively flat, fully demonstrating that the modification layer significantly inhibits dendrite growth, thus improving the battery's cycle stability and safety. Figure 6 ) Example 7: Preparation of modified zinc metal anode: In a glove box with argon atmosphere containing less than 0.1 ppm oxygen and moisture, weigh MnF2 and polyvinylidene fluoride (PVDF), with MnF2 accounting for 15% and PVDF accounting for 60% (solvent: DMSO), and dissolve in DMSO to prepare a homogeneous gel solution. Spin-coat 0.5 mL of this gel solution onto a zinc sheet at a spin coater speed of 2000 r / min for 60 s. After standing and evaporation, allow to evaporate under vacuum (vacuum degree 10). -3 (Drying at 30℃ for 5 hours) yielded an optimized zinc metal anode modified with a composite ion-conducting polymer-zinc fluoride-alloy layer.
[0039] Performance testing: SEM analysis of the modified zinc metal anode revealed a uniform and dense structure formed by the modification layer on the zinc metal anode surface, laying the foundation for improving the performance of the zinc battery. Figure 7 ) Example 8: Preparation of modified zinc metal anode and battery assembly: Under an argon atmosphere in a glove box (oxygen and moisture content below 0.1 ppm), SnF2 and polyvinylidene fluoride (PVDF) were weighed, with SnF2 accounting for 10% and PVDF accounting for 55% (solvent: DMSO), to prepare a homogeneous gel solution. 0.5 mL of this solution was spin-coated onto a zinc sheet using a spin coater with a spin speed of 2000 r / min and a spin time of 60 s. The solution was allowed to stand to evaporate and then vacuum-dried (vacuum degree 10). -3 (Drying at 30°C for 5 hours) yields a modified zinc metal anode. This anode is then assembled into a battery.
[0040] Performance Testing: The electrochemical performance of the battery was studied. The electrochemical cycling performance graph of the symmetrical battery shows that the battery assembled with the modified zinc electrode exhibits improved cycling performance and higher capacity retention during cycling, indicating that the modification layer effectively improves the cycling performance of the zinc battery. Figure 8 ) Example 9: Preparation of modified zinc metal anode and battery assembly: FeF2 and polyvinylidene fluoride (PVDF) were dissolved in polyvinylidene fluoride-difluoropropylene (PVDF-HFP) in a glove box with oxygen and moisture content below 0.1 ppm to prepare a homogeneous gel solution. The solutions were: FeF2 12%, PVDF 50%, and PVDF-HFP 18% (by mass). 0.5 mL of this solution was spin-coated onto a zinc sheet at 2000 rpm for 60 s. The solution was allowed to stand to evaporate and then vacuum-dried (vacuum degree 10). -3 (Drying at 30°C for 5 hours) to obtain a modified zinc metal negative electrode, which is then assembled into a battery.
[0041] Performance testing: The electrochemical deposition dissolution efficiency of the battery was tested. The results showed that the average coulombic efficiency of the modified battery reached 99.03%, significantly higher than that of the original battery. This indicates that the modified layer improved the energy conversion efficiency of the battery and reduced energy loss. Figure 9 ) Example 10: Preparation of modified zinc metal anode and battery assembly: Under an argon atmosphere in a glove box (oxygen and moisture content below 0.1 ppm), YF3 and polyvinylidene fluoride (PVDF) were dissolved in polyvinylidene fluoride-difluoropropylene (PVDF-HFP), with YF3 accounting for 15%, PVDF for 55%, and PVDF-HFP for 10% (by mass ratio) to prepare a uniform gel solution. 0.5 mL of this solution was spin-coated onto a zinc sheet at a spin coater speed of 2000 r / min for 60 s. The solution was allowed to stand to evaporate and then vacuum-dried (vacuum degree 110). -3 (Drying at 30°C for 5 hours) to obtain a modified zinc metal negative electrode, which is then assembled into a battery.
[0042] Performance Testing: The low-temperature electrochemical performance of the battery was studied. The low-temperature electrochemical performance graphs of the battery assembled with the modified electrode show that, under low-temperature conditions, the modified electrode exhibits better electrochemical performance than the original zinc electrode, such as higher discharge capacity and lower polarization. This indicates that the modification layer effectively improves the performance of the zinc battery under low-temperature conditions. Figure 10 ) The preferred embodiments of the present invention disclosed above are only for the purpose of illustrating the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation described herein. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can better understand and utilize the present invention.
Claims
1. A design for a multi-level progressive ion transport interface phase, characterized in that: Includes the following steps: Step 1: Environmental Preparation Replace the atmosphere in the glove box with argon gas to ensure that the oxygen and moisture content in the box are both below 0.1 ppm. Prepare the metal fluoride, polymer, solvent, metal substrate, spin coater and drying equipment required for the experiment. The metal fluoride is one or more of SnF2, ZnF2, MgF2, FeF3, YF3 and MnF2. Step 2: Solution or gel preparation: Weigh out metal fluorides and polymers, and add them to a selected solvent according to a ratio of 0.01%-30% metal fluoride content and 5%-70% organic content. When preparing a modification solution for lithium sheets, mix ZnF2 and PVDF according to a ratio of 10% metal fluoride content, 50% organic content, and the remainder as PVP solvent. When using it for zinc sheets, mix MnF2 and PVDF according to a ratio of 15% metal fluoride content, 60% organic content, and the remainder as DMSO solvent. Step 3: Electrode spin coating: The metal substrate is fixed on the sample stage of the spin coater. 0.5 mL of the prepared solution is drawn up with a pipette and slowly dropped onto the center of the substrate surface. The spin coater is started and the solution is evenly spread on the substrate surface under the action of centrifugal force, forming a thin and uniform liquid film. Step 4: Drying process: After spin coating, remove the electrode with the modification film from the spin coater and place it in the drying area of the glove box. If static drying is used, let the electrode stand for 12 hours to allow the solvent to evaporate naturally. If vacuum treatment is required, place the electrode in a vacuum drying device at a vacuum degree of 10. -3 Drying at 30°C for 5 hours removes residual solvent and cures the modified layer, forming a composite ion-conducting polymer-metal fluoride-alloy layer on the surface of the metal anode.
2. The design of a multi-stage progressive ion transport interface phase according to claim 1, characterized in that: In step two, if multiple metal fluorides are mixed, the ratio between each metal fluoride can be arbitrary, as long as the overall metal fluoride content after mixing is in the range of 0.01%-30%. If multiple polymers are mixed, the ratio between each polymer can also be arbitrary, as long as the overall organic content after mixing is in the range of 5%-70%.
3. The design of a multi-stage progressive ion transport interface phase according to claim 1, characterized in that: In step three, the volume of solution drawn by the pipette can be adjusted from 0.3 to 0.7 mL for metal substrates of different sizes, the rotation speed of the spin coater can be adjusted from 1500 to 2500 r / min, and the rotation time can be adjusted from 45 to 75 s to ensure that a uniform liquid film can be formed on different substrates.
4. The design of a multi-level progressive ion transport interface phase according to claim 1, characterized in that: In step four, for some special combinations of polymers and metal fluorides, if static drying is ineffective, pre-drying in a 40°C oven for 1 hour before static drying, followed by 12 hours of static drying; if vacuum drying is used, for easily oxidized metal fluorides, a vacuum degree of 10 can be applied. -3 After Pa, a small amount of argon gas is introduced into the drying equipment to maintain the pressure at 10. -2 -10 - 1 Between Pa, it is then dried at 30°C for 5 hours.
5. The design of a multi-stage progressive ion transport interface phase according to claim 1, characterized in that: The polymer is one or more of the following polymers: polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene glycol, etc. The solvent includes polyvinylpyrrolidone and dimethyl sulfoxide. The thickness of the metal substrate is between 0.1 and 0.5 mm, and the surface roughness Ra is between 0.05 and 0.2 μm.
6. The design of a multi-stage progressive ion transport interface phase according to claim 1, characterized in that: In step two, a nano-silica dispersion is added, with the amount added being 0.1%-0.5% of the total mass of the solution.
7. The design of a multi-stage progressive ion transport interface phase according to claim 1, characterized in that: In step four, the thickness of the formed composite ion-conducting polymer-metal fluoride-alloy layer is measured. The thickness should be between 50-500 nm. If the thickness does not meet the requirements, the solution concentration, spin-coating parameters and drying conditions can be adjusted according to the actual situation, and the preparation can be repeated.
8. The design of a multi-stage progressive ion transport interface phase according to claim 1, characterized in that: The instruments and equipment used in the preparation process, such as spin coaters, magnetic stirrers, and vacuum drying equipment, need to be calibrated and cleaned before each use to ensure that the performance of the instruments and equipment is stable and that there are no impurities contaminating the experimental materials. In step one, in addition to detecting the oxygen and moisture content in the glove box, the flow rate and purity of argon gas also need to be detected regularly. The argon gas flow rate should be maintained at 5-10 L / min and the purity should not be less than 99.999%.
9. The design of a multi-stage progressive ion transport interface phase according to claim 1, characterized in that: In step two, a magnetic stirrer is used to stir the solution for 3 hours at 40°C and 500 r / min until a uniform solution is formed. In step three, the spin coater rotates at 2000 r / min for 60 seconds.
10. A method for using a multi-level progressive ion transport interface phase according to any one of claims 1-9, characterized in that: Includes the following steps: Step 1: Battery Component Pre-processing and Assembly Under the argon atmosphere in the glove box, the modified metal anode, cathode material and separator are first immersed in the electrolyte for 10-30 minutes to fully wet each component. Using 1M LiTFSI / DME:DOL (1:1) as the electrolyte, the pretreated modified metal anode and the corresponding cathode material and separator are stacked and assembled into a symmetrical cell or a full cell. During the assembly process, the coaxiality deviation of each component is controlled to not exceed 0.5mm. A uniform pressure of 0.1-0.3MPa is applied to ensure good contact between each component and no risk of short circuit. Step Two: Basic Electrochemical Impedance and Reversibility Tests After the assembled battery was statically activated for 24 hours, electrochemical impedance spectroscopy was performed using an electrochemical workstation. The electrochemical impedance spectrum of the battery was obtained under the conditions of frequency range of 0.01Hz-100kHz and amplitude of 5mV. The influence of the modification layer on the interfacial impedance and charge transfer impedance was analyzed. Cyclic voltammetry was performed with the scan rate set to 0.1-1mV / s and the voltage window set according to the battery system. The electrochemical reversibility and interfacial stability of the battery were evaluated by the peak shape, peak position difference and peak area of the redox peak. Step 3: Charge / discharge cycle and rate performance testing: The battery was subjected to constant current charge-discharge cycle tests at a set current density. The charge-discharge specific capacity, initial coulombic efficiency, and coulombic efficiency per cycle were recorded. Rate performance tests were conducted at different current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C, with 5-10 cycles at each current density to evaluate the ion transport capability of the modified layer at different current densities. Long cycle life tests were conducted, with 100-1000 cycles at a 1C current density to examine the battery's capacity retention and interface stability. Step 4: Interface Characterization and Process Parameter Optimization The cycled battery was disassembled, and the morphology, composition, and mechanical properties of the interfacial phase on the surface of the metal anode were characterized using scanning electron microscopy, X-ray photoelectron spectroscopy, and atomic force microscopy. The evolution of the interfacial phase during cycling was analyzed. Based on the electrochemical performance test data and the interfacial characterization results, the solution ratio, spin coating parameters, drying conditions, and battery assembly process parameters in the interfacial phase preparation process were adjusted. The above steps were repeated until battery performance that meets the requirements of practical applications was obtained.